2013
DOI: 10.1111/echo.12440
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Width of the Tracking Area on Speckle Tracking Parameters—Methodological Aspects of Deformation Imaging

Abstract: The strain values determined by 2D speckle tracking are significantly influenced by the tracking area width. The tracking of the subendocardial layers only results in lower global strain values than tracking the complete ventricular wall using the medium or wide tracking area widths. The tracking quality in the far field is worse if the tracking area is too wide. The present data show that standard and reference values of deformation imaging should include detailed information about the position and the width … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Although Mirea et al recently stated that different widths of ROI significantly impact strain measurements, the literature is remarkable sparse on this topic [13]. Stoebe et al found that GLS was significantly influenced by the ROI width in 30 healthy subjects and 15 patients with mild to moderate LV systolic dysfunction [14]. In the healthy group GLS was − 23.5% with narrow, − 20.0% with medium and − 14.6% with wide width.…”
Section: Discussionmentioning
confidence: 99%
“…Although Mirea et al recently stated that different widths of ROI significantly impact strain measurements, the literature is remarkable sparse on this topic [13]. Stoebe et al found that GLS was significantly influenced by the ROI width in 30 healthy subjects and 15 patients with mild to moderate LV systolic dysfunction [14]. In the healthy group GLS was − 23.5% with narrow, − 20.0% with medium and − 14.6% with wide width.…”
Section: Discussionmentioning
confidence: 99%
“…It is import to note that although STE is less angle dependent than TDI measures of strain, the components of longitudinal and circumferential strains are opposite in polarity to radial strain therefore any deviation from the major axis will result in a progressive reduction in strain values in the relative axis (19). In view of this, it is essential to avoid apical foreshortening in the apical views and ensure circular LV chamber in the parasternal short axis (PSAX) views whilst avoiding the use of non-standardised views (20). Suboptimal image acquisition may result in poor speckle tracking.…”
Section: Optimal Image Acquisitionmentioning
confidence: 99%
“…In normal healthy individuals, the inner (subendocardial) layer contributes the most to longitudinal and circumferential strain, with a reduction in the mid-myocardium, and the lowest contribution from the outer (subepicardial) layer (27). Therefore, the width of the ROI has significant effects on the strain values reported (20, 28). If the tracking area width is too narrow, encompassing only the endocardial layer, higher strain values will be reported (28).…”
Section: Image Analysismentioning
confidence: 99%
“…The ROI is the area in the image where speckle tracking occurs, and usually involves some form of delineation of the myocardium. Previous studies of adults have shown that the ROI width affects strain values and therefore is a source of variation for strain measurements [18][19][20]. The effect of ROI width is further nuanced when layer specific strain is taken into account, with ROI width having an increasing impact on strain as one moves from the endocardial to the epicardial layer.…”
Section: Introductionmentioning
confidence: 99%